2014
DOI: 10.1002/term.1875
|View full text |Cite
|
Sign up to set email alerts
|

Generation of composites for bone tissue-engineering applications consisting of gellan gum hydrogels mineralized with calcium and magnesium phosphate phases by enzymatic means

Abstract: Mineralization of hydrogels, desirable for bone regeneration applications, may be achieved enzymatically by incorporation of alkaline phosphatase (ALP). ALP-loaded gellan gum (GG) hydrogels were mineralized by incubation in mineralization media containing calcium and/or magnesium glycerophosphate (CaGP, MgGP). Mineralization media with CaGP:MgGP concentrations 0.1:0, 0.075:0.025, 0.05:0.05, 0.025:0.075 and 0:0.1 (all values mol/dm , denoted A, B, C, D and E, respectively) were compared. Mineral formation was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 73 publications
(87 reference statements)
5
56
1
Order By: Relevance
“…The fact that the areas with cells were roughly spherical suggests that that rMSC adhesion only took place on bioglass particles or aggregates. This observation is in agreement with the findings in previous publications, in which MC3T3‐E1 osteoblast‐like cells displayed poor adhesion on pure GG hydrogels but adhered much better to GG hydrogels enzymatically mineralized with CaP and magnesium‐enriched CaP . In previous work, pure GG hydrogels did not mineralize with apatite upon incubation in SBF, but apatite formed on both GG‐A2 and GG‐S2 hydrogel–bioglass composites .…”
Section: Resultssupporting
confidence: 92%
“…The fact that the areas with cells were roughly spherical suggests that that rMSC adhesion only took place on bioglass particles or aggregates. This observation is in agreement with the findings in previous publications, in which MC3T3‐E1 osteoblast‐like cells displayed poor adhesion on pure GG hydrogels but adhered much better to GG hydrogels enzymatically mineralized with CaP and magnesium‐enriched CaP . In previous work, pure GG hydrogels did not mineralize with apatite upon incubation in SBF, but apatite formed on both GG‐A2 and GG‐S2 hydrogel–bioglass composites .…”
Section: Resultssupporting
confidence: 92%
“…This suggests an increasing amorphicity in the direction A➔E. Characteristic bands for GG at approximately 1,600 and 1,030 cm −1 , which were detected in previous works (Douglas, Krawczyk, et al, , Douglas, Wlodarczyk, et al, , Douglas et al, ), were not observed in any sample group. This demonstrates that a relatively small amount of GG was present relative to the carbonate mineral.…”
Section: Resultssupporting
confidence: 50%
“…Recently, inorganic calcium phosphate (CaP)‐based materials for bone regeneration have been enriched to promote adhesion and proliferation of bone‐forming cells (Bracci et al, , Douglas, Krawczyk, et al, , Landi et al, ). Hence, on the basis of these studies, it was speculated in our study that CaCO 3 enrichment with Mg could lead to similar positive biological effects.…”
Section: Introductionmentioning
confidence: 99%
“…After 42-day culture in chondrogenic medium, cartilaginous ECM components of aggrecan and collagen type II were produced with the confirmation of chondrocytic gene expression [146]. Gellan gum hydrogels incorporated with bioglass/bioceramic particles or bone-forming growth factors were shown to support encapsulation, proliferation, and osteogenesis of preosteoblasts and MSCs for bone tissue regeneration [147149]. Although gellan gum hydrogels are promising for cartilage and bone tissue regeneration, the three key problems may hinder their clinical translations.…”
Section: Designing Hydrogels For Reconstruction Of Osteochondral Imentioning
confidence: 99%